Emotional eating: Really hungry or just angry? - Ekim, Ayfer; Ocakci, Ayse Ferda (Sage Publications Ltd, 2021)
The aim of this study was to investigate the effect of parenting styles and academic self-efficacy on emotional eating behaviours within a sample of adolescents. The sample of this cross-sectionally designed study consisted of 584 adolescents between the ages of 12-17 years. In order to collect necessary data, the Emotional Eating Scale for Child and Adolescent, the Parenting Style Scale and Academic Self-efficacy Scale were utilized. In this sample, Emotional Eating Scale's total score of girls was higher than boys, and emotional eating was not related to body mass index. Parenting styles and academic self-efficacy predicted 34% of the variants seen in emotional eating behaviours of adolescents. While a positive relation existed between emotional eating and negligent parenting style, a negative significant relation occurred between permissive and democratic type of parenting styles and emotional eating. In addition, emotional eating behaviours decreased, whereas academic self-efficacy perception increased accordingly. The results showed that emotional eating behaviours of adolescents were in relation with parenting styles and academic self-efficacy. A good understanding of the multifactorial structure of emotional eating in adolescents will help to develop essential programmes in order to design effective coping mechanisms.
Keywords: Academic; Adolescence; Eating Behaviours; Parenting; Self-Efficacy; Parenting Style; Behavior; Adolescents; Patterns; Children; Weight; Food; Associations; Consumption; Stress